Rilpivirine vs. efavirenz-based single-tablet regimens in treatment-naive adults: week 96 efficacy and safety from a randomized phase 3b study. (January 2016) - van Lunzen, Jan; Antinori, Andrea; Cohen, Calvin J.; Arribas, José R.; Wohl, David A.; Rieger, Armin; Rachlis, Anita; Bloch, Mark; Segal-Maurer, Sorana; Garner, Will; Porter, Danielle; Bosse, Matthew; et al.
Abstract : Objectives: To compare efficacy, safety, tolerability, and patient-reported outcomes between two single-tablet regimens, rilpivirine/emtricitabine/tenofovir disoproxil fumarate (RPV/FTC/TDF) and efavirenz/emtricitabine/tenofovir disoproxil fumarate (EFV/FTC/TDF), in HIV-1-infected, treatment-naive adults. Design: This was a phase 3b, 96-week, randomized, open-label, international, noninferiority trial. Methods: A total of 799 participants were randomized (1 : 1) to receive RPV/FTC/TDF or EFV/FTC/TDF. The primary efficacy endpoint evaluated proportions of participants with HIV-1 RNA less than 50 copies/ml using the Snapshot algorithm. Additional assessments included CD4 + cell counts, genotypic/phenotypic resistance, adverse events, patient-reported outcomes, and quality of life questionnaires. Results: At week 96, trial completion rates were 80.2% (316/394; RPV/FTC/TDF) and 74.0% (290/392; EFV/FTC/TDF). Overall, RPV/FTC/TDF was noninferior to EFV/FTC/TDF [HIV-1 RNA <50 copies/ml: 77.9 vs. 72.4%, respectively; difference –5.5; 95%CI (–0.6, 11.5); P  = 0.076]. RPV/FTC/TDF was significantly more efficacious compared with EFV/FTC/TDF in participants with baseline HIV-1 RNA equal to or less than 100 000 copies/ml (78.8 vs. 71.2%; P  = 0.046) and in those with CD4 + cell count greater than 200 cells/μl (80.6 vs. 73.0%; P  = 0.018). There was no significant between-group difference in the CD4 + cell count increase (278 ± 189 vs. 259 ± 191 cells/μl; P  = 0.17). Few participants developed resistance after week 48 (1.0% RPV/FTC/TDF; 0.3% EFV/FTC/TDF). Compared with EFV/FTC/TDF, RPV/FTC/TDF was associated with fewer adverse event-related discontinuations (3.0 vs. 11.0%; P <0.001), significantly fewer adverse events due to central nervous system issues and rash, greater improvements in patient-reported symptoms, and significant improvements in the SF-12v2 quality of life questionnaire mental health composite score ( P  = 0.014). Conclusion: In treatment-naive, HIV-1-infected participants, 96-week RPV/FTC/TDF treatment demonstrated noninferior efficacy and better tolerability than EFV/FTC/TDF. Abstract : Supplemental Digital Content is available in the text